2008
DOI: 10.1073/pnas.0710676105
|View full text |Cite|
|
Sign up to set email alerts
|

The Coffin–Lowry syndrome-associated protein RSK2 is implicated in calcium-regulated exocytosis through the regulation of PLD1

Abstract: Exocytosis of neurotransmitters and hormones occurs through the fusion of secretory vesicles with the plasma membrane. This highly regulated process involves key proteins, such as SNAREs, and specific lipids at the site of membrane fusion. Phospholipase D (PLD) has recently emerged as a promoter of membrane fusion in various exocytotic events potentially by providing fusogenic cone-shaped phosphatidic acid. We show here that PLD1 is regulated by ribosomal S6 kinase 2 (RSK2)-dependent phosphorylation. RSK2 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…Recent studies in human keratinocytes suggest that the mechanism whereby SCRIB suppresses RAS/MAPK signaling could result from a direct interaction between SCRIB and ERK, which diminishes ERK activation (22). The emerging complexity of SCRIB-mediated regulation of the RAS/MAPK cascade is further illustrated by SCRIB interactions with RSK2, a negative regulator of the pathway (46), and GIT1, an ARF-GAP that can act as a MEK-ERK scaffold (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in human keratinocytes suggest that the mechanism whereby SCRIB suppresses RAS/MAPK signaling could result from a direct interaction between SCRIB and ERK, which diminishes ERK activation (22). The emerging complexity of SCRIB-mediated regulation of the RAS/MAPK cascade is further illustrated by SCRIB interactions with RSK2, a negative regulator of the pathway (46), and GIT1, an ARF-GAP that can act as a MEK-ERK scaffold (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…PtdOH is a key component of the glucose transporter vesicular membrane and the authors demonstrated that PtdOH contributes to the late-stage fusion events. The role of PLD in exocytic events is well PLD and Phosphatidic Acid in Cancer established in neuroendocrine cells (Vitale et al, 2001;Zeniou-Meyer et al, 2008) and similar mechanisms may be at play for glucose transporter vesicle fusion. Besides directly contributing to the biophysics of glucose transporter translocation, PLD also controls expression of glycolytic genes.…”
Section: H Deregulating Cellular Energeticsmentioning
confidence: 99%
“…For example, the p90 ribosomal S6 kinase phosphorylates PLD1 at T147 and this phosphorylation event is required for K + -stimulated PLD activity and exocytosis in PC12 neuroendocrine cells (Zeniou-Meyer et al, 2008). In addition, AMP-activated protein kinase (AMPK) phosphorylates PLD and Phosphatidic Acid in Cancer PLD1 at S505 .…”
Section: A Serine and Threonine Phosphorylationmentioning
confidence: 99%
“…24 Recent data have provided evidence that RSK2 is also a specific modulator of phospholipase D activity in calcium-regulated exocytosis. 25 Rsk2 has, in addition, a specific role in modulating the MAPK-pathway; it exerts a feedback inhibitory effect on the ERK pathway by phosphorylating SOS, which in turn leads to inhibition of Ras. 21 The transcription factor ATF4 (CREB2) was identified as a specific substrate of RSK2 in osteoblasts.…”
Section: Rsk2 Protein Functionmentioning
confidence: 99%